Cooperative compliance : a new approach to managing taxpayer relations - Bronżewska, Katarzyna (Doctoral series, 2016)
This book analyses the concept of cooperative compliance, a relatively new style of cooperation between corporate taxpayers and tax authorities. The growing burden of tax compliance and the inadequate resources provided by tax authorities forced the introduction of a different form of cooperation based on mutual trust, transparency and understanding, while relying on tax risk management. This alternative approach first appeared independently in Australia, Ireland, the Netherlands, the United Kingdom and the United States in the early 2000s. Since then, the concept has been implemented in one form or another in over 20 jurisdictions worldwide. The OECD took the lead on systematizing the concept and in 2008 published a study in which the concept - initially referred to as "enhanced relationship"--Was introduced. A few years on, cooperative compliance is envisioned as a powerful tool to increase the effectiveness of the tax collection process and influence taxpayer behaviour, especially in the post-BEPS environment